Interval and Continuous Training for Resting Pulse and Cardiovascular Enhancement of Students - Rizki Hanif Mahardika; Dwi Cahyo Kartiko; Gigih Siantoro (BIRCU, 2020)
Basketball games are played for 40 minutes divided into 4 quarters, where one quarter is 10 minutes. To play the game of basketball requires having excellent stamina which can be seen from the value of VO₂ Max. There are various types of exercises to improve VO₂ Max, such as interval training and continuous training. The purpose of this study: is to determine the difference in effect between interval training and continuous training on VO₂ Max on basketball players in extracurricular students at Senior high school 2nd Pasuruan City. Research methods: This study used the Pre and Post Test two Groups Design design, with a sample of 12 basketball players as an interval training group, and 12 players as a continuous training group taken using a purposive sample technique. The exercise is done 3 times a week for 8 weeks. Measurement of VO2 Max uses a Multistage fitness test. Data analysis using the comparative test Wilcoxon Signed Ranks test and Mann Whitney test. Results: The difference between pre-test and post-test in the interval training group was 9.94 while in the continuous training group it was 6.02. Based on the test of the effect of interval training on VO₂ Max, the value of p = 0.008 was obtained and the test of the effect of continuous training on VO₂ Max was obtained p value = 0.005. Based on the different test of the effect of interval training and continuous training on VO₂ Max, the value of p = 0.040 is concluded. Conclusion: interval training and continuous training can increase VO₂ Max. interval training increases VO₂ Max more than continuous training in basketball players in extracurricular curricular students at Senior high school.